Milenial, Pemimpin Politik, dan Debat Capres Indonesia 2019 - Firdaus, Mochamad Rizki; Adiprasetio, Justito (Universitas Brawijaya, 2020)
This study tries to explain and the reception of millenial generation in Universitas Padjadjaran towards the representation of leaders in the nonverbal message and the substance of the message of Indonesian Presidential candidates in 2019 presidential debate. Data was collected by in-depth interviews and FGDs of eight informants. The results of this study indicate that the reading of informants on the representation of the leaders of the candidates for the substance and nonverbal candidates in the 2019 Indonesian Presidential Debate shows candidate 01 superior to candidate 02. Candidate 01 excels in five variables: nonverbal kinesik, nonverbal artifactual, substance alignment topics, substance selection and alternative solution arguments, and the substance of the stimulation of alternative solutions. Whereas candidate 02 is only one variable superior namely nonverbal paralinguistic.